Whither mankind : (Longmans, Green and Co., 1928)
This volume is a challenge, not a summary of fragile dubiosities. No mystery hangs over it. Undẻlying it is the assumption that science and the machine are two invincible facts with which all must rekon who write, teach, preach, lead, or practice the arts in our time.